Implementation of Sustainable Tourism in Kertalangu Cultural Village as a Tourist Attraction in Denpasar City - Chandradewi, Anindya; Hadiwijoyo, Suryo Sakti; Simanjuntak, Triesanto Romulo (CV. Publikasi Indonesia, 2024)
This research aims to describe how Sustainable Tourism is implemented in the Kertalangu Cultural Village as a tourist attraction in Denpasar City. Researchers used qualitative research methods with primary data collection techniques obtained directly through observation, interviews and official data published by the Denpasar City Tourism Office, in this case in the form of the number of tourist visits to the Kertalangu Cultural Village from 2018 to 2023 as well as secondary data collected obtained through literature study. This research uses the concept of Sustainable Tourism and tourism aspects are analyzed using constructivism theory. The research results show that the implementation of Sustainable Tourism in the Kertalangu Cultural Village has been successful. This success is proven by an increase in tourist visits by 37.33% in 2023 and the development of natural potential and improvements to facilities. This makes the Kertalangu Cultural Village able to attract tourists to visit, making it a tourist attraction with Sustainable Tourism.